Citizen science survey of the snake’s head fritillary (Fritillaria meleagris) in the valley of the river Zala in Hungary - Búzás, Előd; Bódis, Judit; Fülöp, Bence; Pacsai, Bálint (GEORGIKON FOR AGRICULTURE, 2022)
The protected snake’s head fritillary (Fritillaria meleagris) is an easily recognisable plant species, and therefore allows for botanical monitoring through socially based or communitybased ’citizen science’. Agro-technical interventions for spring grassland management can cause severe damage to the species. It is therefore important to have as accurate and up-to-date data base as possible of the species’ distribution and abundance. Our target area was the Alsó-Zala-völgy Special Area of Conservation (Natura 2000). Students, PhD students and lecturers of the Georgikon Campus of the Hungarian University of Agriculture and Life Sciences, along with the Association for Land and People NGO assisted the survey, which was carried out between 4 and 15 April 2022. In total 23 participants counted or estimated the number of flowering plants of fritillary in 1607 localities along the River Zala. They surveyed 1500 hectares of grasslands. The records from this survey were shown on a map of the species’ current distribution in the area. That will be a great use for the Balaton-felvidéki National Park Directorate in its work. The students participating in the monitoring survey had the opportunity to gain experience in data collection and to understand the importance of extensive grassland management and the complexity of conservation work through the target species.